A structural equation modeling associating obesity and body dissatisfaction with health-related biopsychosocial parameters in adolescents - Simões, Caroline Ferraz; Junior, Nelson Nardo; Locatelli, João Carlos; de Souza Mendes, Victor Hugo; de Oliveira, Gustavo Henrique; Werneck, André Oliveira [UNESP]; dos Santos, Tamires Leal Cordeiro; Remor, Jane Maria; Oliveira, Ronano Pereira; Lopes, Wendell Arthur (Springer Nature, 2021)
This cross-sectional study investigated the associations of obesity and body dissatisfaction (BD) with health-related biopsychosocial parameters in adolescents, and the magnitude of these associations. The sample was composed of 239 overweight/obese adolescents aged between 15 and 18 years. Data was analyzed by means of a structural equation model, composed of obesity as the exogenous variable and five endogenous variables: BD, health-related quality of life (HRQoL), physical fitness (PF), readiness for behavior change (RBC), and eating habits. The model adjustment indicators were considered adequate (RMSEA =.03, χ2(df) = 124.6(94), CFI =.96, TLI =.95, GFI =.94). We identified a direct and negative relationship between obesity and BD (r = −.698, p <.001), and a direct relationship between these variables and HRQoL (Obesity: r = −.539, p <.001; BD: r = −.563, p <.001), PF (Obesity: r = −.424, p =.015; BD: r = −.393, p =.020), RBC (Obesity: r = −.445, p =.10; BD: r = −.448, p =.007), and eating habits (Obesity: r =.311, p =.032; BD: r =.363, p =.028). BD seems to play an important mediating role in health-related biopsychosocial parameters in adolescents. In addition, the negative consequences of BD on HRQoL, PF, eating habits and RBC appear to occur in a similar magnitude to those caused by obesity itself.
Keywords: Adolescent health; Biopsychosocial parameters; Body image; Obesity; Overweight